Mechanical engineering and materials science : selected, peer reviewed papers from the 2011 international conference on mechanical engineering and materials science (ICMEMS 2011), September 24-25, 2011, Cheju Island, Korea - Tan, Barry (Applied mechanics and materials ;, 2012)
This set comprises selected peer-reviewed papers from the 2011 International Conference on Mechanical Engineering and Materials Science (ICMEMS 2011), held on September 24-25th, 2011, at Cheju Island, Korea. The objective of ICMEMS 2011 was to provide a forum where researchers, educators, engineers, and government officials involved in the above fields could circulate their latest research results and exchange ideas concerning the expected future research directions of these fields. The work is thus a timely guide to the topic. Review from Book News Inc.: This collection of fifty-seven article.